141 Can coping strategies alleviate the link between workplace aggression and burnout? the role of seeking instrumental or emotional socal support. (24th April 2018) - Delvaux, Ellen; Brande, Whitney Van den; Schouteden, Martijn; Sercu, Maarten; Baillien, Elfi; Broeck, Anja Van den; Godderis, Lode
Abstract : Introduction: Aggression at the workplace occurs frequently. Workplace aggression negatively impacts employees' psychological well-being. In the current research, we investigated whether coping strategies alleviated the negative impact of workplace aggression on one important indicator of employees' psychological well-being, namely burnout (risk). More specifically, we examined whether the coping strategies seeking instrumental or emotional social support moderated the relationship between workplace aggression and burnout symptoms. Methods: Questionnaires were administered to employees of a large Belgian hospital. In total, 1544 employees participated (response rate=44%). The scale measuring workplace aggression consisted of three items (α=0, 79). Burnout risk was measured with the two most central subscales of the Dutch version of the Maslach Burnout Inventory (UBOS), namely emotional exhaustion (5 items; α=0, 92) and depersonalization (4 items; α=0, 86). Finally, from the COPE questionnaire, we used the subscales seeking instrumental social support (4 items; α=0, 92) and emotional social support (4 items; α=0, 92). We tested our hypotheses using hierarchical regression analyses. Result: Replicating previous research, we found that workplace aggression increases both the levels of emotional exhaustion and depersonalization. Furthermore, we found that seeking instrumental social support is a better coping strategy than seeking emotional social support: the former decreases burnout symptoms, whereas the latter may even increase burnout symptoms. Finally, we found that the coping strategy seeking instrumental social support alleviated the relationship between workplace aggression on the one hand and emotional exhaustion and depersonalization on the other. Seeking emotional social support only moderated the relationship between workplace aggression and depersonalization: the level of depersonalization increased for employees with lower scores on this coping strategy when they encountered workplace aggression; employees scoring high on this coping strategy had increased levels of depersonalization regardless of experienced workplace aggression. Discussion: Our findings will be discussed in light of its theoretical and practical contributions.